Implementasi Metode Z-Score Altman, Zmijewski dan Grover Dalam Memprediksi Financial Distress PT Garuda Indonesia (Persero) Tbk. Periode 2017-2020 - Gian Nandana (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2022)
This study aims to predict the financial distress condition of PT Garuda Indonesia (Persero) Tbk in the 2017-2020 period by implementing the Altman, Zmijewski and Grover Z-Score method. This research is descriptive with qualitative data analysis. The results of this study PT Garuda Indonesia (Persero) Tbk. obtaining poor results, the three methods used include the Altman Z-Score, Zmijewski and Grover methods showing the same results that the company is in financial distress or is in serious financial difficulty and is in danger of causing bankruptcy in the 2017- 2020 period. Of course this is for the management of the company a special concern to improve the condition of the company in a better direction such as improving the financial condition of the utilization of assets owned by PT Garuda Indonesia (Persero) Tbk.